Curcumin Encapsulated in Crosslinked Cyclodextrin Nanoparticles Enables Immediate Inhibition of Cell Growth and Efficient Killing of Cancer Cells - Karin Möller; Beth Macaulay; Thomas Bein (Nanomaterials, 2021)
The efficiency of anti-cancer drugs is commonly determined by endpoint assays after extended incubation times, often after days. Here we demonstrate that curcumin encapsulated in crosslinked cyclodextrin nanoparticles (CD-NP) acts extremely rapidly on cell metabolism resulting in an immediate and complete inhibition of cell growth and in efficient cancer-cell killing only few hours after incubation. This early onset of anti-cancer action was discovered by live-cell high-throughput fluorescence microscopy using an environmental stage. To date, only very few examples of covalently crosslinked nanoscale CD-based (CD-NP) drug carriers exist. Crosslinking cyclodextrins enables the adsorption of unusually high payloads of hydrophobic curcumin (762 µg CC/mg CD-NP) reflecting a molar ratio of 2.3:1 curcumin to cyclodextrin. We have investigated the effect of CD-NP encapsulated curcumin (CD-CC-NP) in comparison to free, DMSO-derived curcumin nanoparticles (CC-NP) on 4 different cell lines. Very short incubations times as low as 1 h were applied and cell responses after medium change were subsequently followed over two days. We show that cell proliferation is inhibited nearly immediately in all cell lines and that a cell- and concentration dependent cancer-cell killing occurs. Anti-cancer effects were similar with free and encapsulated curcumin, however, encapsulation in CD-NP drastically extends the long-term photostability and anti-cancer activity of curcumin. Curcumin-sensitivity is highest in HeLa cells reaching up to 90% cell death under these conditions. Sensitivity decreased from HeLa to T24 to MDA MB-231 cells. Strikingly, the immortalized non-cancerous cell line MCF-10A was robust against curcumin concentrations that were highly toxic to the other cell lines. Our results underline the potential of curcumin as gentle and yet effective natural anti-cancer agent when delivered solvent-free in stabilizing and biocompatible drug carriers such as CD-NP that enable efficient cellular delivery.